2018
DOI: 10.1016/j.appet.2017.11.101
|View full text |Cite
|
Sign up to set email alerts
|

Effect of snack-food proximity on intake in general population samples with higher and lower cognitive resource

Abstract: ObjectivePlacing snack-food further away from people consistently decreases its consumption (“proximity effect”). However, given diet-related health inequalities, it is important to know whether interventions that alter food proximity have potential to change behaviour regardless of cognitive resource (capacity for self-control). This is often lower in those in lower socio-economic positions, who also tend to have less healthy diet-related behaviours. Study 1 aims to replicate the proximity effect in a general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
64
0
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 56 publications
6
64
0
1
Order By: Relevance
“…Given that Shiv and Fedorikhin found that the effect of cognitive load in their study was only apparent when actual foods were presented [ 33 ], repeating this element of the study with choices between physically-present foods would be valuable. Nevertheless, the lack of effect may indicate that cognitive load did not influence people’s choice of food, as has previously been demonstrated in studies of food proximity [ 47 ]. This could suggest that altering the availability of healthier and less healthy food impacts behaviour without requiring cognitive resource, such as response inhibition, as has been hypothesised for interventions targeting physical micro-environments [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 93%
“…Given that Shiv and Fedorikhin found that the effect of cognitive load in their study was only apparent when actual foods were presented [ 33 ], repeating this element of the study with choices between physically-present foods would be valuable. Nevertheless, the lack of effect may indicate that cognitive load did not influence people’s choice of food, as has previously been demonstrated in studies of food proximity [ 47 ]. This could suggest that altering the availability of healthier and less healthy food impacts behaviour without requiring cognitive resource, such as response inhibition, as has been hypothesised for interventions targeting physical micro-environments [ 3 , 9 ].…”
Section: Discussionmentioning
confidence: 93%
“…It has been hypothesised that because interventions that manipulate environmental cues do not rely on people consciously engaging and forming intentions to change their behaviour, their effects will not be moderated by executive function, specifically response inhibition. Because executive function resources are patterned by SEP, tending to be lower in lower SEP groups [12,13], this may also mean that SEP would not moderate the effect of such interventions (although SEP could modify these associations in other ways). The purpose of examining moderation by these two variables is therefore to give a preliminary indication of the intervention's potential to change behaviour in a way that does not exacerbate health inequalities, as an absence of moderation would suggest the intervention is similarly effective in those with varying levels of cognitive resource [4,12].…”
Section: Introductionmentioning
confidence: 99%
“…Because executive function resources are patterned by SEP, tending to be lower in lower SEP groups [12,13], this may also mean that SEP would not moderate the effect of such interventions (although SEP could modify these associations in other ways). The purpose of examining moderation by these two variables is therefore to give a preliminary indication of the intervention's potential to change behaviour in a way that does not exacerbate health inequalities, as an absence of moderation would suggest the intervention is similarly effective in those with varying levels of cognitive resource [4,12]. Regarding sensitivity to perceptual cues, being more sensitive to external (relative to internal) cues could feasibly result in manipulations of environmental cues such as plate size having a greater impact, although to our knowledge no previous research has directly tested this.…”
Section: Introductionmentioning
confidence: 99%
“…The relevance of such research is underlined by studies that have demonstrated an association between the increased density of fast-food outlets and increased incidences of cardiovascular diseases and unhealthy lifestyles [ 16 ]. Experimental lab studies have indeed confirmed that the proximity of unhealthy snacks, typically within arm’s reach, increases the likelihood of unhealthy snack consumption [ 17 , 18 , 19 ]. However, studies have also found that placing healthy snacks in greater proximity increases the consumption of these healthier products.…”
Section: Problems Arising From the Food Environmentmentioning
confidence: 99%